Accidental IV administration of epinephrine instead of midazolam at colonoscopy - Ahmed Gado; Basel Ebeid; Anthony Axon (Alexandria Journal of Medicine, 2016)
Drug administration errors appear to be a major source of iatrogenic harm to hospitalized patients. They often, particularly in the case of epinephrine, have catastrophic consequences both for the patient and the well-meaning provider. The following incident is a medication error case report which illustrates one way that incorrect medication may be administered. IV epinephrine was accidentally administered instead of midazolam at colonoscopy.